Implementation of Word Wall Web in Language Learning: How Does It Impact Students' Vocabulary Mastery? - Iftitah, A.N; Sunubi, Abdul Haris; Asiza, Nur; Zulfah; Natsir Maulana, Muhammad (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
This study aims to enhance students' vocabulary mastery by proposing the Word Wall Web as a learning medium. The research employed a quantitative method with a quasi-experimental design, incorporating pre-test and post-test evaluations. The participants consisted of 63 students, divided into two groups: a control class (n=32) and an experimental class (n=31). Students' understanding of pronouns, nouns, adjectives, and verbs was evaluated through 20 multiple-choice questions, covering various formats such as synonyms, antonyms, fill-in-the-blank, word substitution, and translation. The control class recorded an average pre-test score of 66.14, which increased to 72.26 in the post-test. In contrast, the experimental class exhibited a more substantial improvement, with an average pre-test score of 64.38, rising to 78.22 in the post-test. Statistical analysis of the post-test mean difference between the experimental and control groups yielded a p-value of 0.003, which is less than the significance level of 0.05, indicating a statistically significant difference at the 95% confidence level. Students in the experimental class who utilized the Word Wall Web demonstrated greater interest in learning, active participation, and improved vocabulary mastery compared to those in the control class. These results underscore the effectiveness of the Word Wall Web as a learning medium for enhancing students' vocabulary mastery.